Activated human monocytes inhibit the intracellular multiplication of legionnaires’ disease bacteria - Horwitz, MA (The Rockefeller University Press, 1981)
We have examined the interaction between virulent egg yolk-grown L. pneumophila, Philadelphia 1 strain, and in vitro-activated human monocytes, under antibiotic-free conditions. Freshly explanted human monocytes activated by incubation with concanavalin A (Con A) and human lymphocytes inhibited the intracellular multiplication of L. pneumophila. Both Con A and lymphocytes were required for activation. Con A was consistently maximally effective at greater than or equal to 4 μg/ml. Monocytes activated by incubation with cell-free filtered supernatant from Con A-sensitized mononuclear cell cultures also inhibited the intracellular multiplication of L. pneumophil a. The most potent supernatant was obtained from mononuclear cell cultures incubated with greater than or equal to 15 μg/ml Con A for 48 h. The degree of monocyte inhibition of L. pneumophila multiplication was proportional to the length of time monocytes were preincubated with supernatant (48 {greater than} 24 {greater than} 12 h) and to the concentration of supernatant added (40 percent {greater than} 20 percent {greater than} 10 percent {greater than} 5 percent). Monocytes treated with supernatant daily were more inhibitory than monocytes treated initially only. With time in culture, monocytes progressively lost a limited degree of spontaneous inhibitory capacity and also lost their capacity to respond to supernatant with inhibition of L. pneumophila multiplication. Supernatant-activated monocytes inhibited L. pneumophila multiplication in two ways. They phagocytosed fewer bacteria, and they slowed the rate of intracellular multiplication of bacteria that were internalized. As was the case with nonactivated monocytes, antibody had no effect on the rate of intracellular multiplication in supernatant-activated monocytes. Neither supernatant-activated nor nonactivated monocytes killed L. pneumophila in the absence of antibody. Both killed a limited proportion of these bacteria in the presence of antibody and complement. We have previously reported that anti-L, pneumophila antibody and complement neither promote effective killing of L. pneumophila by human polymorphonuclear leukocytes and monocytes nor inhibit the rate of L. pneumophila multiplication in monocytes. These findings and our present report that activated monocytes do inhibit L. pneumophila multiplication indicate that cell-mediated immunity plays a major role in host defense against Legionnaires’ disease.